Evaluación estacional de la reproducción de esteroides sexuales en testiculos del ratón de orejas oscuras (Peromyscus melanotis Allen & Chapman, 1897) de diferentes clases de edad - Salame-Méndez, Arturo; Castro-Campillo, Alondra; Salgado-Ugarte, Isaías; Mendieta-Márquez, Enrique; Herrera-Muñoz, Joaquín; Ramírez-Pulido, José (Instituto de Ecología, A.C., 2020)
The local, altitudinal and vegetational distributions of the superfamily Papilionoidea were studied in 37 localities of the Sierra Nevada. Estimate richness was of 91 species, using species accumulation curves. As a result of this work 75 species were found, 34 of which were new records for the area. An updated species list (85 taxa) was elaborated adding reports of previous works. The Nymphalidae had the greatest number of species. The spatial analysis of the Papilionoidea showed that the highest richness and abundance occurred in the locality of Santa Catarina, México State. In spite of the similarities of the specific richness between occidental and oriental slopes, their faunistic composition were different. The species of the Papilionoidea were greatest in the oriental slope, andthe cloud and Quercus forest have the highest value in richness and abundance among the 11 vegetational communities recognized.